MENGINTEGRASIKAN TEKNOLOGI DIGITAL DALAM PEMBELAJARAN DI MI/SD PADA ERA REVOLUSI INDUSTRI 5.0 - April Lailia, Shinta; Fatimah, Siti; Seftiana, Afil Fres; Ayu, Sri; Rista, Vesti Nurmala (Pusat Studi Ekonomi Publikasi Ilmiah dan Pengembangan SDM, 2023)
This research aims to explore appropriate media and methods for the application of digital technology in schools, with a focus on MI/SD education. Several examples of supportive media, such as Quizizz, Wordwall, Zoom, and Gmeet, were considered. Through interviews with MI/SD teachers, this research identified challenges and barriers to integrating digital technology in schools. The results show that improving teachers' knowledge and skills is key to overcoming these challenges. Teachers need to be able to apply developmentally appropriate methods and media in the industrial 5.0 era. In addition, improving school infrastructure is also an important factor in overcoming barriers to integrating digital technology. In order to improve the quality and relevance of the learning experience, the solution proposed in this study is to improve teachers' knowledge and skills through training and professional development that focuses on the application of digital technology. In addition, it is necessary to improve school infrastructure to support the effective use of digital technology. With the implementation of these solutions, it is expected that MI/SD education can continue to innovate and adapt to current technological developments. This will ensure that students' learning experiences become more qualified and relevant to the demands of evolving times. Keywords: Digital technology, Learning, MI/SD, Industrial revolution 5.0.